The role of the 90-kDa heat shock protein in cell cycle control and differentiation of the monoblastoid cell line U937. - Galea-Lauri, J; Latchman, D; Katz, DR (1996)
The human monoblastoid cell line, U937, has been widely used to study proliferation and differentiation in the monocyte-macrophage lineage. Recent evidence from other cell systems suggests that heat shock proteins (hsps) may participate in these processes. Therefore, we have examined expression of hsp and the effect of either increased or decreased expression of the hsp90 in U937 cells. Parental U937 cells express high levels of hsp90, hsp73, and hsp65, but little hsp72. Heat shock at 42 degrees C for 30 min increased hsp72 levels but caused no change in hsp90. U937 cells transfected with the expression vector pBA.4 containing either an anti-sense or a sense hsp90 cDNA insert showed constitutive decrease, or increase, in expression of hsp90. Decreased hsp90 levels slowed the rate of cell division and levels of hsp90 correlated both with the responses to phorbol esters and with phenotypic changes: antisense-transfected cells expressed less CD50. Sense-transfected cells showed no change in cell cycle, but expressed less CD14 than controls. Thus, hsp90 plays a role in the monocyte-macrophage lineage, participating in proliferation and cell cycle control and in the acquisition of functional heterogeneity of the mature macrophage phenotype, with potential effects on the role of the macrophage in innate immunity.